2020
DOI: 10.1016/j.joen.2020.07.007
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Apical Periodontitis and Conventional Nonsurgical Root Canal Treatment in General Adult Population: An Updated Systematic Review and Meta-analysis of Cross-sectional Studies Published between 2012 and 2020

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 95 publications
(137 reference statements)
2
86
2
7
Order By: Relevance
“…As well as many studies, the present study revealed that both of the root canal filling and coronal restoration quality are equally important for the periapical health in endodontically treated teeth [9,33]. According to the present study, when the root canal filling was inadequate, the good coronal seal did not prevent AP in endodontically treated teeth (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…As well as many studies, the present study revealed that both of the root canal filling and coronal restoration quality are equally important for the periapical health in endodontically treated teeth [9,33]. According to the present study, when the root canal filling was inadequate, the good coronal seal did not prevent AP in endodontically treated teeth (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…5% of endodontically treated teeth with inadequate root canal treatment, and AP in their study was significantly associated with insufficient root canal fillings (P < 0.05) [5]. Moreover, in a Meta-analysis of previous crosssectional studies published between 2012 and 2020, Jakovljevich et al, had shown a significant higher prevalence of AP in treated teeth with inadequate root canal treatment (OR = 4.65; 95% CI 2.75-7.84; p < 0.00001), and a significant higher prevalence of AP in ETT with poor coronal restoration (OR = 1.54; 95% CI 1.16-2.05, p = 0.003) [9], these findings are all in accordance with the results of the present study. The interpretation of radiographs is the most common method used to evaluate AP in epidemiological studies [11,34], clinical symptoms such as pain, swelling, sinus tract formation and tenderness are moderately specific.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occasionally, lesions in the periapical region can also develop due to nonodontogenic causes (Rodrigues & Estrela 2008, Moraes Ramos-Perez et al 2010. Jakovljevic et al (2020) in their systematic review reported that 6.3% of teeth in the general adult population had apical periodontitis.…”
Section: Introductionmentioning
confidence: 99%